Pembelajaran Bahasa Inggris pada Lembaga Kursus dan Pelatihan (LKP) Ambisco Metro Lampung - Hans, Diah Maulidya (Institut Teknologi Pendidikan Indonesia, 2023)
This study aims to investigate English learning at AMBISCO as the course and training institute by concentrating on analyzing English learning strategies applied in each English course program at AMBISCO. This research was conducted based on the development of LKP AMBISCO both in terms of quantity and quality, of course,participants in the middle of competition with various other English courses in Metro city, Lampung. This research uses a descriptive qualitative method. Data collection techniques are interviews, observation, and documentation. The results of the study show that learning English at AMBISCO is administrated by implementing English learning strategies which are broadly divided into the initial learning phase, the main learning phase, and the final learning phase. Learning strategies in each English course program are applied effectively based on the need analysis of participants in each program so that they can achieve the learning target effectively.